Evaluasi Proyek Pembangunan Kelapa Sawit Pola Kredit Koperasi Primer untuk Anggota (KKPA) PT. Padasa Enam Utama Bekerjasama dengan Petani Kemitraan Di Kabupaten Kampar Riau - Supriyanto Supriyanto; Amir Hasan; Vince Ratnawati (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
This study aims to determine the general picture of farmers both corporate and non-partner partners, find out and analyze the attributes that are priorities for partner farmers in participating in the partnership program, find out the impact of the partnership implementation program on the progress of partner farmers and to find out and analyze the attributes performance attributes that must be improved. The research activity was carried out at PT PEU's plantation located in Koto Kampar Hulu Subdistrict, Kampar Regency, Riau Province. Data collection was carried out for 5 months starting from January to May 2017. The research method to be carried out was a survey method using data documentation. The sampling technique was divided into two, namely farmers who participated in the partnership program as many as 100 respondents and farmers who did not participate in the partnership program were 50 respondents. The data processing method is to use description analysis, thurstone analysis, sign test, gross margin, chi square, and quadrant analysis. Based on the results of the study it can be concluded that several suggestions are: (1). An important issue that must be considered is the issue of trust, which according to the results of research the trust of partner farmers to the company has been seen to fall, therefore the company is expected to grow the trust of partners where one of them is to seriously implement the agreement. (2) The company can provide an understanding and explanation to partner farmers that in the long run this program can have good prospects where farmers do not need to think about the cost of caring for the garden and it is easy to get good seeds, (3) Need to improve the system of recording FFB produced by farmers so that farmers can know the number of FFB produced accurately.